Recombinant polymerase amplification combined with lateral flow strips for the detection of deep-seated Candida krusei infections - Zhao, Mengdi; Wang, Xizhen; Wang, Kun; Li, Yuanyuan; Wang, Yan; Zhou, Ping; Wang, Lei; Zhu, Wenjun (Frontiers in Cellular and Infection Microbiology, 2022)
The incidence of Candida infections in intensive care units (ICU) has significantly increased in recent years, and these infections have become one of the most serious complications threatening the lives of ICU patients. The proportion of non-Candida albicans infections, such as Candida krusei and Candida glabrata infections, which are resistant to fluconazole, is increasing each year. Early identification of the strains causing Candida infections is important for the timely implementation of targeted treatments to save patients’ lives. However, the current methods of direct microscopy, culture, and histopathology, as well as other diagnostic methods, have many shortcomings, such as their low sensitivity and long assay times; therefore, they cannot meet the needs for early clinical diagnosis. Recombinant polymerase amplification (RPA) is a promising isothermal amplification technique that can be performed without sophisticated instruments and equipment, and is suitable for use in resource-poor areas. RPA combined with lateral flow strips (LFS) can be used to rapidly amplify and visualize target genes within 20 min. In this study, RPA-LFS was used to amplify the internal transcribed spacer 2 (ITS2) region of C. krusei. The primer-probe design was optimized by introduction of base mismatches (probe modification of five bases) to obtain a specific and sensitive primer-probe combination for the detection of clinical specimens. Thirty-five common clinical pathogens were tested with RPA-LFS to determine the specificity of the detection system. The RPA-LFS system specifically detected C. krusei without cross-reaction with other fungi or bacteria. A gradient dilution of the template was tested to explore the lower limit of detection and sensitivity of the assay. The sensitivity was 10 CFU/50 µL per reaction, without interference from genomic DNA of other species. The RPA-LFS and qPCR assays were performed on 189 clinical specimens to evaluate the detection performance of the RPA-LFS system. Seventy-six specimens were identified as C. krusei, indicating a detection rate of 40.2%. The results were consistent with those of qPCR and conventional culture methods. The RPA-LFS system established in our study provides a reliable molecular diagnostic method for the detection of C. krusei, thus meeting the urgent need for rapid, specific, sensitive, and portable clinical field testing.